Structure and legitimizing of the crime of collusion and impunity in the judicial district of Huánuco - Vásquez-Solís, Leoncio E. (2019)
The crime of collusion is a special offense that demands for the correct determination of imputation knowledge extrapenal standards set illicit, however, due to the complexity of the pre-defined crime of collusion rules, and the need of such offenses punishable which seriously affects the normal development of the state public finance system, the legislature has had to resort to a set of legal amendments that result has meant that the current legal formula that regulates the crime of collusion provisions of Article 384º of the Penal Code, there is structure in the context of their crimes sources such as the crimes of breach of duty, and also is not legitimate because it seeks to punish dangerous behavior aside the end ratio and subsidiary that inspire the Peruvian Penal Code, is why, at the end of this investigation show that the regulation of the Crime of Collusion to date is only a sample of desperate measure but no real solution and curb acts of corruption committed in the State procurements made leading to impunity and mistrust in the Peruvian legal system procurement.